Intelligent Drilling Depth Monitoring System for Geotechnical Site Investigation. (30th May 2022) - Huang, Man; Chen, Zhangwei; Hong, Chenjie; Sha, Peng; Wu, Zaosheng; Hu, Chundong; Tao, Zhigang
Abstract : The drillhole depth is an indispensable parameter in the exploration process of drilling and coring engineering, but it is mainly calculated by manually counting the number of drill pipes. This highly subjective measurement method can easily lead to artificially misreporting borehole drillhole depth data, making the geological information mismatch. This study presents the overall scheme design of intelligent drillhole depth monitoring and designs real-time acquisition equipment and an installation device. The designed drillhole depth monitoring system is applied in the engineering investigation of a school laboratory expansion. In accordance with the collected data on site, the variation law of the drilling rig in the soil layer and the calculation formula of the drillhole depth are obtained. In addition, it is validated that the monitoring system can also be used well in the rock layer geology. Therefore, the proposed monitoring method is more reliable and convenient than the traditional calculation method of drillhole depth, which could serve as a reference for the intelligent drilling field management.